Marker assisted selection and segregation distortion studies in rice (Oryza sativa) - MANJAPPA, GANIGER; UDAY, GOVINDAREDDY; HITTALMANI, SHAILAJA; KRISHNAPPA, GOPALAREDDY (The Indian Journal of Agricultural Sciences, 2022)
Rice (Oryza sativa L.) is an important staple food crop and is grown across different regions and moisture regimes across Asian countries. The present study was carried out during rainy (kharif) season 2017–19 for introgressing genes, raising F1 plants, evaluation of F2 plants and marker distortion studies at Marker Assisted Selection Laboratory, University of Agricultural sciences, Bangalore. True F1 plants were confirmed using polymorphic SSR marker RM242 and selfed to develop F2 plants. Marker assisted identification using 11 trait specific SSR markers linked to higher contributing alleles for drought, blast and bacterial leaf blight (BLB) resistance in F2 population was derived from a japonica variety Moroberekan and indica variety IR 64. F2 population exhibited highly significant segregation distortions for four (36.4%) out of 11 SSR markers. Out of four distorted markers, RM242 and RM235 were towards IR64 (male parent) and RM11943 and RM243 distorted towards heterozygote and Moroberekan (female parent), respectively. The allele frequency and distribution of genotype frequencies in the F2 population were analyzed for SSR markers, to find out factors that attributed to segregation distortion. Three markers (RM11943, RM243 and RM235) showed distorted allele frequency, with normal genotype frequency and one showed distorted genotype frequency with normal allele frequency, which indicates that these markers were influenced at gametic and zygotic level, respectively.